Prevalence of uremic pruritus in chronic kidney patients undergoing maintenance hemodialysis at Kathmandu Medical College Teaching Hospital - Adhikari, Laxman; Kayastha, Rajat; Bhatta, Karuna (Journal of Kathmandu Medical College, 2017)
Background: Uremic pruritus is a common and troublesome symptom of chronic kidney disease. It is one of the dominant dermatological manifestations of chronic kidney disease which affects the quality of life of patients. Objective: To assess the prevalence and severity of uremic pruritus in chronic kidney disease patients undergoing maintenance hemodialysis. Methodology: A prospective cross-sectional study was done over three months among chronic kidney patients undergoing maintenance hemodialysis to show the association of mineral bone disorders with uremic pruritus. Patients complaining of pruritus were taken as cases and then pruritus was quantified using a Visual Analogue Scale. Results: 144 patients participated in this study, out of which 41 (28.47%) were females. Mean age was 54.97±9.75 years and 68.06% patients were on dialysis. Uremic pruritus was seen in 80 patients (55.56%), amongst them 23 patients (28.75 %) had severe pruritus as measured by Visual Analogue Scale. Uremic pruritus was more frequent and more severe in patients having higher serum phosphorus levels (p =0.004). Conclusion: This study further substantiates the need of adequate control of phosphorus levels in hemodialysis patients to reduce complications like uremic pruritus. Journal of Kathmandu Medical College, Vol. 5, No. 4, Issue 18, Oct.-Dec., 2016, Page: 124-127